2021
DOI: 10.3390/pharmaceutics13071008
|View full text |Cite
|
Sign up to set email alerts
|

Development and Optimization of Cinnamon Oil Nanoemulgel for Enhancement of Solubility and Evaluation of Antibacterial, Antifungal and Analgesic Effects against Oral Microbiota

Abstract: Oral health is a key contributor to a person’s overall health and well-being. Oral microbiota can pose a serious threat to oral health. Thus, the present study aimed to develop a cinnamon oil (CO)-loaded nanoemulsion gel (NEG1) to enhance the solubilization of oil within the oral cavity, which will enhance its antibacterial, antifungal, and analgesic actions against oral microbiota. For this purpose, the CO-loaded nanoemulsion (CO-NE) was optimized using I-optimal response surface design. A mixture of Pluracar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…The instantaneous emulsification capacity and clarity of the prepared LV-Eu-SNEDDS were used to assess the NE efficiency via visual inspection [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The instantaneous emulsification capacity and clarity of the prepared LV-Eu-SNEDDS were used to assess the NE efficiency via visual inspection [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…enzymatic degradation, (3) promoting drug loading, solubility, and pharmacokinetic features, (4) diminishing interpatient and intrapatient variations, and (5) controlling the release of studied drugs [30,31].…”
Section: Estimation Of LV Solubility In Various Snedds Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…One milliliter of each lyophilized sample – which was first reconstituted with 5 mL double distilled water – was diluted with 9 mL of distilled water and agitated for 3 min. Then, 1 mL of each diluted sample was used to determine the particle size and polydispersity index (PDI) of each NLCs formulation (Hosny KM et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro release of eugenol, from nanoemulgel, showed an enhanced release compared with that of pure CO. The studies finally revealed that the ex vivo mucosal permeation was found to be highest for nanoemulgel compared to the aqueous dispersion of cinnamon oil nanoemulsion and pure cinnamon oil [24].…”
Section: Antibacterial Antifungal and Analgesic Effects Against Oral ...mentioning
confidence: 99%